Efficient capture of radioactive iodine by a two-dimensional metal-organic framework - Jiaxing Deng; Xingwei Xie; Pengjun Duan; Xiang Ni; Chaoxiang Liu; Hanya Zheng; Rong Cheng; Xiang Zheng; Jianzhong Zheng (Chemical Engineering Journal, 2026)

Nanostructured Fe2(MoO4)3 cathodes: Enhancing ion and electron kinetics for high-rate and low-temperature sodium-ion batteries - Ting Zhao; Hang Liu; Gacao Dou; Dongting Zhang; Junqiang Qiao; Juan Yang; Pengjun Ma; Cuiying Lu; Hongxia Li; Hongruo Ma; Kunjie Wang; Bingjun Yang (Chemical Engineering Journal, 2026)

Integrative analysis of Huangjing-Gegen compatibility in treating COPD: a network pharmacology, molecular docking, and experimental study - Shaoqing Zhu; Jiaruo Li; Lin Chu; Yunpeng Zhu; Wei Wang; Man Wang; Zhenhua Zhu; Fei Mao; Pengjun Liu; Ying Chu (Natural Product Research, 2026)

Do maritime safety actions deliver lasting risk reduction? Evidence from AIS-based near-miss analysis using difference-in-differences - Tunan Xu; Yifei Mao; Manel Grifoll; Jiao Liu; Yingheng Zhang; Pengjun Zheng (Frontiers in Marine Science, 2026)
Maritime administrations frequently implement short-term intensive safety actions to mitigate collision risk in mixed commercial–fishing traffic waters. However, empirical evidence on their effectiveness remains limited because maritime accidents are rare and behavior-level risk indicators are not routinely incorporated into policy evaluation. This study develops an AIS-based evaluation framework that uses monthly near-miss counts as a behavior-level proxy of navigational risk and combines this proxy with a difference-in-differences (DID) design to assess a maritime special safety action in Ningbo–Zhoushan waters. Using large-scale AIS trajectory data, near-miss events are identified based on DCPA and TCPA criteria and then aggregated to the sea area–month level. The analysis covers 9 sea areas from January to December 2023 (108 observations). In the baseline two-way fixed-effects specification, the coefficient on Treat × Post is positive but statistically insignificant (β = 0.4094, SE = 0.2581), indicating that the intervention did not produce robust evidence of a reduction in the AIS-based near-miss indicator. Event-study estimates likewise show no statistically significant persistent dynamic treatment effect within the observation window. These findings suggest that, under the proxy measure and identification strategy used in this study, the special safety action did not generate a clearly identifiable reduction in near-miss counts in treated waters. Methodologically, the study demonstrates the practical value of combining AIS-derived behavioral indicators with quasi-experimental policy evaluation. At the same time, the results should be interpreted with caution, because near-miss counts are structurally related to traffic intensity and traffic composition, and the policy period overlaps with the seasonal fishing moratorium. The proposed framework nevertheless offers a useful basis for evidence-based evaluation of non-engineering maritime safety interventions in complex mixed-traffic environments.

A Data-Driven Framework for Detecting Unsafe Ship–Bridge Passages Based on AIS Trajectories - Qiyang Li; Hongzhu Zhou; Jiao Liu; Yibing Wang; Manel Grifoll; Pengjun Zheng (Journal of Marine Science and Engineering, 2026)
Ship–bridge collisions in cross-sea bridge waterways are rare but potentially catastrophic events, making conventional accident-based risk assessment difficult to implement effectively. Existing AIS-based indicators capture vessel behaviors but insufficiently quantify bridge-passage safety margins, especially dynamic aspects such as crossing posture and readiness prior to bridge transit. To address this limitation, this study proposes a data-driven framework for detecting unsafe ship–bridge passages using two bridge-passage-oriented surrogate safety measures (SSMs) and extreme value theory (EVT). The Bridge-passage Lateral Clearance Margin (BLCM) quantifies the effective lateral safety margin retained during the realized bridge-crossing stage, while the Bridge-passage Readiness Lead Time (BRLT) measures how early a vessel becomes stably prepared for bridge passage before crossing. The Peaks Over Threshold (POT) model is first used to characterize the marginal extremes of the two indicators, and a bivariate threshold exceedance model (BTE) is then established to examine their joint risk behavior. Case studies of the Jintang Bridge and Zhoudai Bridge waterways demonstrate that the proposed framework can effectively screen and identify trajectories with unsafe or margin-deficient bridge-passage characteristics. The results show that unsafe passages are typically associated with both reduced lateral clearance and insufficient preparation time, and that joint modeling of the two indicators improves risk identification performance. The findings suggest that ship–bridge risk is better interpreted from the perspective of passage quality deficiency rather than simple geometric proximity. The proposed framework provides an interpretable tool for retrospective unsafe passage screening, traffic monitoring support, and post-event safety analysis in complex bridge waterways.

Port carbon emission reduction strategies under government incentive-based regulation: An evolutionary game analysis - Kainan Zhang; Hangying Lou; Yuting Xia; Pei He; Pengjun Zheng; Guiyun Liu (Journal of Cleaner Production, 2026)

Nitrogen fertilizer strategies modulate gaseous nitrogen losses and improve maize yield and nitrogen use efficiency under saline-alkali stress in coastal reclaimed farmland - Xiaoqing Wang; Jiayi Xie; Wenjing Li; Lijie Pu; Pengjun Chen; Jijun Han; Chenliang Du; Sihua Huang; Rui Zhang; Rui Zhong; Ye Yuan; Jiahao Zhai; et al. (Soil and Tillage Research, 2026)

Quantifying ship-bridge collision risk through extreme value theory: a new methodological framework - Xi Chen; Hongzhu Zhou; Meng Li; Manel Grifoll; Yusheng Zhou; Jiao Liu; Pengjun Zheng (Ocean Engineering, 2026)

Triple parallel rolling circle amplification aid DNA hydrogel/QDs-based programmable aptasensor for targets profiling - Ying Xiong; Yue Wang; Xin Jiang; Xianghu Zeng; Pengjun Jiang; Bofu Liu; Binwu Ying; Yi Xie; Piaopiao Chen (Chemical Engineering Journal, 2025)

Temperature-responsive composite delivery system with efficient epidermal adhesion for enhanced insecticidal activity - Meixue Sun; Yingjie Liu; Yonghui Zhang; Wenlong Feng; Hailin Yang; Guangwei Ren; Pengjun Xu; Xiufang Wang; Chenyu Su (Chemical Engineering Journal, 2025)

Fabrication of copper(II)-doped nanocarriers with pathogen-responsive properties for enhanced fungicidal activity - Yahui Yang; Yonghui Zhang; Yingjie Liu; Lifang Wang; Wenlong Feng; Xiufang Wang; Guangwei Ren; Pengjun Xu; Yong Gu; Chenyu Su (Chemical Engineering Journal, 2025)

MixSegNext: A CNN-Transformer hybrid model for semantic segmentation and picking point localization algorithm of Sichuan pepper in natural environments - Pengjun Xiang; Fei Pan; Tao Liu; Xiaoyu Zhao; Mengdie Hu; Dawei He; Boda Zhang (Computers and Electronics in Agriculture, 2025)

Synergistic leaching-regeneration strategy for the recovery of valuable metals from spent LIBs - Ni Ai; Wenye Deng; Yi Liu; Penggao Liu; Pengjun Zhao; Aimin Chang; Yongxin Xie (Process Safety and Environmental Protection, 2025)

Molecularly engineered BiO-BDC-NH2 interface for high-performance carbon-electrode perovskite photovoltaics - Min Liu; Zhenwu Zhong; Jian Cheng; Yaxin Wei; Pengjun Zhao; Ying Qi; Hongyu Mi; Shengzhong Liu; Haijiao Xie; Yahong Xie (Chemical Engineering Journal, 2025)

Trajectory prediction model of a ship crossing under a bridge based on multi-head attention mechanism and Wasserstein GAN with gradient penalty - Jiao Liu; Kaige Zhu; Yaqing Shu; Yuanqiang Zhang; Pengjun Zheng (Ocean Engineering, 2025)

A Transformer–VAE Approach for Detecting Ship Trajectory Anomalies in Cross-Sea Bridge Areas - Jiawei Hou; Hongzhu Zhou; Manel Grifoll; Yusheng Zhou; Jiao Liu; Yun Ye; Pengjun Zheng (Journal of Marine Science and Engineering, 2025)
Abnormal ship navigation behaviors in cross-sea bridge waters pose significant threats to maritime safety, creating a critical need for accurate anomaly detection methods. Ship AIS trajectory data contain complex temporal features but often lack explicit labels. Most existing anomaly detection methods heavily rely on labeled or semi-supervised data, thus limiting their applicability in scenarios involving completely unlabeled ship trajectory data. Furthermore, these methods struggle to capture long-term temporal dependencies inherent in trajectory data. To address these limitations, this study proposes an unsupervised trajectory anomaly detection model combining a transformer architecture with a variational autoencoder (transformer–VAE). By training on large volumes of unlabeled normal trajectory data, the transformer–VAE employs a multi-head self-attention mechanism to model both local and global temporal relationships within the latent feature space. This approach significantly enhances the model’s ability to learn and reconstruct normal trajectory patterns, with reconstruction errors serving as the criterion for anomaly detection. Experimental results show that the transformer–VAE outperforms conventional VAE and LSTM–VAE in reconstruction accuracy and achieves better detection balance and robustness compared to LSTM–-VAE and transformer–GAN in anomaly detection. The model effectively identifies abnormal behaviors such as sudden changes in speed, heading, and trajectory deviation under fully unsupervised conditions. Preliminary experiments using the POT method validate the feasibility of dynamic thresholding, enhancing the model’s adaptability in complex maritime environments. Overall, the proposed approach enables early identification and proactive warning of potential risks, contributing to improved maritime traffic safety.

Preparation of thermally sensitive ceramics by co-precipitation of mixed acid-soaked spent LIBs: Experimental methods, structure and mechanism - Ni Ai; Wenye Deng; Yi Liu; Yan Xue; Jinyang Li; Kai Ding; Pengjun Zhao; Aimin Chang; Penggao Liu; Yongxin Xie (Journal of Environmental Chemical Engineering, 2025)

Exploring collective activity space and its spatial heterogeneity using mobile phone signaling Data: A case of Shenzhen, China - Juan Li; Pengjun Zhao; Mengzhu Zhang; Yiling Deng; Qiyang Liu; Yanzhe Cui; Zhaoya Gong; Juan Liu; Wenchang Tan (Travel Behaviour and Society, 2025)

Highly selective and effective ferroptosis liposomal nanodrugs for synergistic antitumor therapy - Huan Xin; Pengjun Yuan; Yujing Wang; Jianmin Xiao; Geng Tian; Yong Fan; Guilong Zhang; Lu Liu (Chemical Engineering Journal, 2024)

Villagers' travel burden and the built environment in rural China: Evidence from a national level survey - Dandan Yuan; Pengjun Zhao; Zhao Yu; Qiyang Liu (Journal of Transport Geography, 2023)

Characterization and genomic analysis of a novel bacteriophage BUCT_49532 lysing Klebsiella pneumoniae - Guangye Zhang; Yucong Liu; Jinhong Wang; Nan Li; Pengjun Han; Yiming Chen; Weijian Xu; Changxia Liu (Virus Genes, 2023)

Exploring the spatial characteristics of the human mobility network in rural settings of China's Greater Bay Area - Zhengying Liu; Pengjun Zhao; Qiyang Liu; Yanzhe Cui; Yuan Yang; Juan Liu; Buhui Li; Jingwei Li (Journal of Transport Geography, 2023)

Circulation of Development Factors Promoted by Innovation of Land Management Under Background of Rural Vitalization: A Case Study of Tengtou Village in Zhejiang Province, China - Pengjun Wei; Yongqiang Liu; Jinlong Yan; Meiting Li; Yingnan Zhang (Chinese Geographical Science, 2023)

Efficient decolorization of melanoidin in raw molasses wastewater by thermophilic esterase in actual extreme conditions - Zedong Zhang; Wanting Hu; Qiuyue Xie; Yuezhe Shi; Yutong Zhao; Yaxin Deng; Jiaxin He; Xia Wu; Yu Zhang; Wenqi Zhang; Pengjun Liu; Hao Yang; et al. (Bioresource Technology, 2023)

Dynamic analysis of a low-carbon maritime supply chain considering government policies and social preferences - Xingyu Huang; Guiyun Liu; Pengjun Zheng (Ocean & Coastal Management, 2023)

The effects of urban land use on energy-related CO2 emissions in China - Tingting Kang; Han Wang; Zhangyuan He; Zhengying Liu; Yang Ren; Pengjun Zhao (Science of The Total Environment, 2023)

The living environment and intravillage activity-travel: A conceptual framework based on participant observation in Guangdong, China - Qiyang Liu; Zhengying Liu; Zhao Yu; Pengjun Zhao (Journal of Rural Studies, 2023)

Anomalous Ru dissolution enabling efficient integrated CO2 electroreduction in strong acid - Beibei Sheng; Dengfeng Cao; Hongwei Shou; Wenjie Xu; Chuanqiang Wu; Pengjun Zhang; Chongjing Liu; Yujian Xia; Xiaojun Wu; Shengqi Chu; Jing Zhang; Li Song; et al. (Chemical Engineering Journal, 2023)

Complete organellar genomes and molecular phylogeny of Hypnea cervicornis (Gigartinales, Florideophyceae) from China - Yu Xia; Pengjun Liu; Xiaoquan Liu; Jing Zhang; Xinfeng Tan; Xuli Jia; Yuemei Jin; Tao Liu; Yue Hu (Journal of Applied Phycology, 2022)

The Relationship of Morphological-Hemodynamic Characteristics, Inflammation, and Remodeling of Aneurysm Wall in Unruptured Intracranial Aneurysms - Qingyuan Liu; Yisen Zhang; Junhua Yang; Yi Yang; Maogui Li; Shanwen Chen; Pengjun Jiang; Nuochuan Wang; Yanan Zhang; Jia Liu; Jun Wu; Shuo Wang (Translational Stroke Research, 2022)

Effects of Preparedness on Successful Emergency Response to Ship Accident Pollution Using a Bayesian Network - Yini Zhu; Wenqing Ma; Hongxiang Feng; Guiyun Liu; Pengjun Zheng (Journal of Marine Science and Engineering, 2022)
With the rapid development of international trade and the fast growth of port freight volumes, the risk of ship pollution in marine areas has significantly increased. Frequent ship pollution accidents seriously endanger marine ecosystems and are extremely unfavorable to economic development and marine environmental protection. In this study, we investigate the results of emergency responses after ship pollution accidents and analyze the factors affecting a successful emergency response. A Bayesian network model of the emergency response results of ship pollution is established, and the emergency response results of ship pollution accidents in the example of Zhoushan Port are analyzed. Based on the analysis, suggestions for strengthening the emergency preparedness of Zhoushan Port are proposed. We believe that the results of this are beneficial for improving ship pollution risk management and decision making, and that they have practical significance for marine environmental protection.

Quantitative source identification and apportionment of heavy metals under two different land use types: comparison of two receptor models APCS-MLR and PMF - Min Zhang; Xueping Wang; Chang Liu; Jiayu Lu; Yuhong Qin; Yunkan Mo; Pengjun Xiao; Ying Liu (Environmental Science and Pollution Research, 2020)

Sequencing and phylogenetic characterization of a novel Polerovirus from Nicotiana tabacum - Yingjie Liu; Yonghao Dong; Xi Chen; Yun Zang; Jinyan Liu; Guangwei Ren; Pengjun Xu (Virus Genes, 2020)

Sequencing and phylogenetic characterization of a novel RNA virus genome from Harmonia axyridis - Yingjie Liu; Guangwei Ren; Lianqiang Jiang; Changchun Feng; Dongyang Liu; Yongjie Liu; Pengjun Xu (Molecular Biology Reports, 2020)

Identification of the heavy metal pollution sources in the rhizosphere soil of farmland irrigated by the Yellow River using PMF analysis combined with multiple analysis methods—using Zhongwei city, Ningxia, as an example - Min Zhang; Xueping Wang; Chang Liu; Jiayu Lu; Yuhong Qin; Yunkan Mo; Pengjun Xiao; Ying Liu (Environmental Science and Pollution Research, 2020)

Preference of the aphid Myzus persicae (Hemiptera: Aphididae) for tobacco plants at specific stages of potato virus Y infection - Jinyan Liu; Yingjie Liu; Philip Donkersley; Yonghao Dong; Xi Chen; Yun Zang; Pengjun Xu; Guangwei Ren (Archives of Virology, 2019)

Characterization of a novel RNA virus from Nesidiocoris tenuis related to members of the genus Iflavirus - Yonghao Dong; Jiangtao Chao; Jinyan Liu; Annabel Rice; Robert Holdbrook; Yongjie Liu; Pengjun Xu (Archives of Virology, 2018)

Structural proteins of Helicoverpa armigera densovirus 2 enhance transcription of viral genes through transactivation - Pengjun Xu; He Yuan; Xianming Yang; Robert I. Graham; Kaiyu Liu; Kongming Wu (Archives of Virology, 2017)

Spectroscopic Identification of Interactions of Pb2+ with Bovine Serum Albumin - Yihong Liu; Lijun Zhang; Rutao Liu; Pengjun Zhang (Journal of Fluorescence, 2012)

Effects of the antibiotic growth promoters flavomycin and florfenicol on the autochthonous intestinal microbiota of hybrid tilapia (Oreochromis niloticus ♀ × O. aureus ♂) - Suxu He; Zhigang Zhou; Yuchun Liu; Yanan Cao; Kun Meng; Pengjun Shi; Bin Yao; Einar Ringø (Archives of Microbiology, 2010)

Molecular cloning and characterization of four heat shock protein genes from Macrocentrus cingulum (Hymenoptera: Braconidae) - Pengjun Xu; Jinhua Xiao; Li Liu; Tong Li; Dawei Huang (Molecular Biology Reports, 2010)

Spectroscopic Investigation on the Toxicological Interactions of 4-aminoantipyrine with Bovine Hemoglobin - Yue Teng; Rutao Liu; Shifeng Yan; Xingren Pan; Pengjun Zhang; Meijie Wang (Journal of Fluorescence, 2010)

Gene cloning, expression and characterization of an α-galactosidase from Pedobacter nyackensis MJ11 CGMCC 2503 with potential as an aquatic feed additive - Xiaodan Liu; Kun Meng; Yaru Wang; Pengjun Shi; Tiezheng Yuan; Peilong Yang; Huiying Luo; Yingguo Bai; Bin Yao (World Journal of Microbiology and Biotechnology, 2009)